Convergent feature and interactive travel journalism opportunity - Negizbaeva М.О.; Kanapiyanova Э.К. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2020)
The article discusses current issues in the field of travel journalism, travel and contextual media and their place in modern society. The practice of travel journalism is still largely ignored as an area of research for communication and journalism researchers. Despite this, many researchers refute this theory and make strong arguments about the relevance and importance of the role of travel journalism in journalism science and practice. For example, this study has studied the opinions of journalistic travelers and scientific works of scientists in the field of media tourism and communication. The purpose of the article is to highlight the convergent feature and interactive opportunity of travel journalism. A literature review will allow you to see the picture of the transition of researchers’ interest from the topic of the seriousness of travel journalism to the issues of effective interactivity with the audience. The review contains research materials from Western, European, and post-Soviet countries. The work contains cases on travel blogs in social networks, which determine the success and effectiveness of travel media data in popularizing travel. As part of the research, a sociological survey was conducted to determine the attitude of modern society to the travel-context media under the new technical possibilities. The result of the survey made it possible to determine the current state of the travel context media in the society and outline their role in journalism. In addition, for the sake of interest in the scientific article, a SWOT analysis was compiled, which compares traditional and new media, using the example of TV shows and social networks. The practical significance of the survey lies in the analysis of advantages and disadvantages of travel context media on the global and domestic media markets.